Path Analysis of Teachers’ Cognitive Activation and Students’ Mathematics Achievement in PISA 2022 Indonesia - Kismiantini; Earthadara, Salma Calista (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
PISA 2022 data show that Indonesian students’ mathematics performance remains low, with an average score of 366 and ranking 70th out of 81 participating countries. This highlights the need to identify factors influencing students’ mathematics achievement. Based on the teaching quality framework, cognitive activation is considered the most influential dimension in improving mathematics performance because it encourages students to think deeply, reason conceptually, and solve complex problems, beyond the effects of teacher support or classroom management. Previous studies mainly examined direct relationships among variables, while this study adds the mediating roles of disciplinary climate, teacher support, and proactive mathematics behavior as a form of contextual adaptation. This quantitative study used data from PISA 2022 Indonesia involving 13,439 students from 410 schools, with 12,209 students providing complete responses. Data were analyzed using a path mediation model based on structural equation modeling (SEM) with maximum likelihood estimation, and standard errors were obtained from 1,000 bootstrap samples. Model validation was conducted through confirmatory factor analysis, showing good model fit with CFI > 0.90 and RMSEA < 0.08. The results indicate that cognitive activation and gender have both direct and indirect effects on mathematics achievement through disciplinary climate and proactive behavior. Socioeconomic and cultural status also influence achievement through proactive mathematics behavior. Male students scored lower in disciplinary climate, proactive behavior, and mathematics performance compared to female students. These findings emphasize the importance of cognitively activating instruction and teacher capacity-building policies to foster disciplined, supportive learning environments that enhance students’ mathematical reasoning.